Inside the mind of an EPO examiner. (September 2018) - Lahorte, Philippe
Abstract: This article provides an insight into the thinking of EPO examiners during the search process and how examiners balance high quality with service and efficiency. At the basis for high-quality search and examination lies the consistent and transparent application of the legal concepts and procedures defined by and following the European Patent Convention (EPC). This article addresses the key questions how examiners come to an understanding of the invention and how they dissect the claims and develop search and examination strategies. Finally, this article illustrates that – like other highly specialized knowledge workers – the job of a patent examiner is highly complex and entails many challenges. Experienced examiners not only apply their technical and legal expertise. They also exercise sound judgment and decision-making skills, work strategically and adopt a strong service orientation.